(untitled) - Zubay, Geoffrey L (Dubuque, Iowa, 1995)
This book is a concise introductory text intended for use in one-semester biochemistry courses. The book contains coverage of both the biological and chemical aspects of the subject, enabling the student to understand the relationship between biology, chemistry and biochemistry. It features new colour molecluar graphic images of important biological molecules which have been generated specifically for inclusion in the text with the introductory level student in mind
Keywords: Biochemistry